Optoelectronic Properties of Chloro- and Fluoro- Boron Subphthalocyanine Derivatives: Theoretical, Synthetic and Spectral Studies - Schultheiss, Alexander; Taylor, Darlene K. (Current Physical Chemistry, 2017)
Aims: Experimental and computational studies of a series of multi-halogenated boron subphthalocyanine (Cl-BsubPcXn) derivatives are reported. This family of compounds with various degrees of chlorine or fluorine peripheral substitution (n = 4, 8, or 12) was studied by density functional theory (B3LYP model) in order to characterize the optimized geometries and electronic structures. Method: The boron subphthalocyanines with one, two and three fully fluorinated rings (Cl- BsubPcF4, Cl-BsubPc F8, and Cl-BsubPcF12 respectively) were prepared in a single pot synthesis, purified, and characterized. Observation: While the yields (0.6%, 5.2%, 1.9% respectively) are low, this is the first report of isolated separation and characterization of these subphthalocyanine structures. Result: Absorption spectroscopy and electrochemical studies confirmed that the ring substitution has a strong effect on the electronic properties of Cl-BsubPcXn. Cyclic voltammetry and UV-Vis support theoretical results where bandgaps decreased as the degree of fluorine substitution increased.
Keywords: Subphthalocyanines